Mitigating the photodegradation of all-inorganic mixed-halide perovskite nanocrystals by ligand exchange. Issue 18 (25th April 2022) - Wahl, Jan; Haizmann, Philipp; Kirsch, Christopher; Frecot, Rene; Mukharamova, Nastasia; Assalauova, Dameli; Kim, Young Yong; Zaluzhnyy, Ivan; Chassé, Thomas; Vartanyants, Ivan A.; Peisert, Heiko; Scheele, Marcus
Abstract : We show that the decomposition of caesium lead halide perovskite nanocrystals under continuous X-ray illumination depends on the surface ligand. Abstract : We show that the decomposition of caesium lead halide perovskite nanocrystals under continuous X-ray illumination depends on the surface ligand. For oleic acid/oleylamine, we observe a fast decay accompanied by the formation of elemental lead and halogen. Upon surface functionalization with a metal porphyrin derivative, the decay is markedly slower and involves the disproportionation of lead to Pb 0 and Pb 3+ . In both cases, the decomposition is preceded by a contraction of the atomic lattice, which appears to initiate the decay. We find that the metal porphyrin derivative induces a strong surface dipole on the nanocrystals, which we hold responsible for the altered and slower decomposition pathway. These results are important for application of lead halide perovskite nanocrystals in X-ray scintillators.